Finishing work case study: double storeys terrace at Laman Annur, Panji, Kota Bharu / Noor Aniza Ismail - Ismail, Noor Aniza (Universiti Teknologi MARA, Perak, 2013)
In this practical report contains information about the selected case study of the finishing word process. This report I do base on observation, interview and experiences about 4 month practical training. This report was be started by introduction of company background and followed by company profile, organisation chart and project has been undertaken. The company that I have chosen to do practical training is Pasir Puteh Development Corporation Sdn.Bhd. In this report also give information about case study during practical training. The process of finishing work can be divided by into four groups such as floor finishing, wall finishing, roof finishing, and ceiling finishing. The finishes process is importance to show the value of the building. It also can be used to the building because to protect and to keep the span of building. Base on case study, the floor finishes have also four type and material such as ceramics, tile, cement render and timber strip. In this report will be all the information about it and also the process the installation of finishes. Besides that, in practical report also provide the material and apparatus was be used at case study. It are use to get easy do the work and to avoid the waste time. Time is one case of importance during the construction work. So that, by using the modern material in construction work can be saved time it include can save the cost. In addition, in this report some problem has be provide base on case study. One example of problem is the installation of roof. It can be effect when rainy days because the water will be enter through hole and will be effect to wall and ceiling. By the way, all the problem must be have answer include the problem that have also followed by recommendation. Overall, in this practical report will give all the information about the finishing work process was done which is can be give new knowledge.